(untitled) - Dierolf, Thomas (Indonesia, 2001)
Contents: The acid, upland soil farming environment in Southeast Asia; cyclical process and practical tools to improve soil fertility management in acid, uplan soils; principles and methods; essential information for extension workers.
Phân bón và khuyến cáo bón phân
Keywords: Soil fertility,Thổ nhưỡng